COMPARATIVE ANALYSIS OF PRIMARY AND RECYCLED POLYMERS USING FTIR SPECTROSCOPY AND THERMAL METHODS - Muratova Shoxista Nimatullaevna,; Khalilova Laylokhon Ikrom qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This study presents a comparative analysis of primary and recycled polymers utilizing Fourier-transform infrared (FTIR) spectroscopy and thermal analysis methods, specifically Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA). As global plastic recycling intensifies, understanding the structural degradation and thermal stability shifts in recycled matrices becomes crucial for maintaining material performance. FTIR spectroscopy was employed to monitor structural changes, identifying specific functional group degradation, such as carbonyl formation due to photo-oxidation and mechanical stress during reprocessing. Thermal methods evaluated the alterations in crystallinity, melting behavior, and thermal decomposition pathways. The results demonstrate that while recycled polymers retain primary chemical structures, degradation-induced chain scission reduces overall thermal stability and crystallinity compared to their virgin counterparts. These findings provide critical insights for optimizing blending ratios and stabilizing additives in high-value secondary polymer applications